2011
DOI: 10.3989/redc.2011.1.794
|View full text |Cite
|
Sign up to set email alerts
|

Análisis bibliométrico de la situación de las mujeres investigadoras de Ciencias Sociales y Jurídicas en España

Abstract: Resumen: Se presenta un estudio bibliométrico cuyo objetivo es analizar la productividad y la citación de las investigadoras en las Ciencias Sociales y Jurídicas en España en el marco de las revistas científi cas nacionales. Como fuente de información se han empleado los rankings de investigadores/as presentes en el Índice de Impacto de las Revistas Españolas de Ciencias Sociales (INRECS) y el Índice de Impacto de las Revistas Españolas de Ciencias Jurídicas (INRECJ). El estudio analiza 11 disciplinas científi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
7
0
11
Order By: Relevance
“…On the other hand, as argued by Bordons, Morrillo, Fernández and Gómez (2003), women's production rises as they gain access to higher positions in university ranks, this being noticeable in the second five-year period, with an increasing presence of women in editorial teams and as large and medium-sized producers. These results fall into contradiction with studies that found men to be more productive versus women (Abramo, D'Angelo and Caprasecca, 2009;Aksnes et al 2011;Larivière, Vignola Gagné, Villeneuve, Gelinas and Gingras, 2011;Maz-Machado et al 2012;Torres-Salinas et al 2011). It should be noted that in period 2009-2013, the number of women considered large producers (5 or more articles) is also higher than that in [2004][2005][2006][2007][2008].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…On the other hand, as argued by Bordons, Morrillo, Fernández and Gómez (2003), women's production rises as they gain access to higher positions in university ranks, this being noticeable in the second five-year period, with an increasing presence of women in editorial teams and as large and medium-sized producers. These results fall into contradiction with studies that found men to be more productive versus women (Abramo, D'Angelo and Caprasecca, 2009;Aksnes et al 2011;Larivière, Vignola Gagné, Villeneuve, Gelinas and Gingras, 2011;Maz-Machado et al 2012;Torres-Salinas et al 2011). It should be noted that in period 2009-2013, the number of women considered large producers (5 or more articles) is also higher than that in [2004][2005][2006][2007][2008].…”
Section: Discussionmentioning
confidence: 58%
“…When scientific production in educational psychology is compared between the period 2004-2008 and the period 2009-2013 from a gender perspective, women have a higher presence in both. Although during 2004-2008, men's scientific production in this discipline was higher, the trend was reversed between 2009-2013, women standing out production-wise, which can be explained by their later access to university education (Aksnes, Rorstad, Piro and Siversten, 2011;Sierra, Buela-Casal, Bermúdez and Santos-Iglesias, 2009;Torres-Salinas, Muñoz-Muñoz and Jiménez-Contreras, 2011), which would justify their lower production in the first period. On the other hand, as argued by Bordons, Morrillo, Fernández and Gómez (2003), women's production rises as they gain access to higher positions in university ranks, this being noticeable in the second five-year period, with an increasing presence of women in editorial teams and as large and medium-sized producers.…”
Section: Discussionmentioning
confidence: 99%
“…Una singularidad importante de la revista, al igual que ocurre en los Congresos de la Sociedad (López et al, 2017), es la elevada presencia de mujeres en las publicaciones, su activa productividad, su posicionamiento en el orden de firma, y su impacto diferencial en la comunidad científica, y en el Consejo Editorial (González-Sala y Osca-Lluch, 2018). Define una revista muy sensible al género frente a la situación general del ámbito donde los hombres doblan a las mujeres en producción de documentos y firman más en primera posición (Barrios, Villarroya y Borrego, 2013;González-Alcaide et al, 2010;Torres-Salinas, Muñoz-Muñoz y Jiménez-Contreras, 2011;Sierra, Buela-Casal, Bermúdez y Santos, 2009;Velasco, Vilariño, Amado y Fariña, 2014).…”
Section: Artículosunclassified
“…Llama la atención estos resultados si tenemos en cuenta que en España en el área de Psicología Evolutiva y de la Educación en el año 2011, el número de mujeres como personal docente investigador era mayor, representando el 62,7% dentro de esta área de conocimiento, frente a un 37,3% que son hombres (Instituto Nacional de Estadística, 2014), aspecto también señalado por Fong et al (2009), si bien como señala Torres-Salinas et al (2011), se ha de tener en cuenta la entrada reciente de la mujer en la universidad, lo cual puede estar detrás de una menor producción y de una menor presencia como grandes y medianas productoras.…”
Section: Conclusionesunclassified
“…En este sentido, según un estudio de la Fundación Española para la Ciencia y la Tecnología (2013) a partir del año 2002, la producción científica española muestra un crecimiento acelerado, llegando a duplicarse en el año 2010 con respecto a la producción del año 2001, y se considera que la calidad de la producción científica española va a seguir incrementándose. Las técnicas bibliométricas también se han empleado para el estudio de la productividad científica según el género (Barrios, Villaroya y Borrego, 2013;Bermúdez et al, 2011;Sierra, Buela-Casal, Bermúdez y Pablos-Iglesias, 2009;Torres-Salinas, Muñoz-Muñoz y Jiménez-Contreras, 2011;Velasco, Vilariño, Amado y Fariña, 2014), en el estudio de la composición de los comités editoriales de las revistas científicas (González-Sala, Fonseca-Baeza y Osca-Lluch, 2014; Mauleón, Hillán, Moreno, Gómez y Bordons, 2013), en la financiación por comunidades (Buela-Casal et al, 2013), en la calidad de las universidades españolas según su implicación social, labor investigadora y función docente (Beamonte, Casino y Veres, 2013), entre otros. Todo ello ha contribuido a un aumento en el número de tesis doctorales relacionadas directamente con la bibliometría (Osca-Lluch, Haba, Fonseca, Civera y Tortosa, 2013).…”
Section: Introductionunclassified